Adherence to antiretroviral therapy in children in Zimbabwe: a randomized control trial to validate a new self-reported adherence monitoring tool - Mugore, Linnetie (Rhodes University, Faculty of Pharmacy, Pharmacy, 2014)
Background: Among children taking antiretroviral therapy (ART), self-reports have been widely reported to over-estimate adherence levels. Pill count adherence levels are often lower than self-reported levels, with unannounced home pill count adherence being lower than facility based pill count adherence. There is often poor agreement between pill count adherence levels and those measured using other objective adherence measuring methods such as Medication Event Monitoring Systems (MEMSÂ®), which is widely viewed as the gold standard for adherence measurement. Objectives: The aim of this study was to design and evaluate a new self-reported paediatric adherence monitoring tool, assess the feasibility of using pill count methods in monitoring adherence and identify challenges to reporting adherence among children on ART in rural and urban Zimbabwe. Methods A dual centre, superiority, parallel design RCT was conducted to evaluate the newly-developed visually- and verbally-cued past 10 days"Ÿ tool for the assessment of adherence in children on ART at two sites in Zimbabwe; Harare Central Children"Ÿs Hospital in an urban setting, and Murambinda Mission Hospital, a rural site. Child-caregiver pairs presenting to one of these facilities for the child"Ÿs review of ART and refill of the medication were recruited, signed informed consent obtained, and were randomised for self-reported adherence monitoring into either the experimental group (new 10-day tool"Ÿ) or the control group (PACTG-style"Ÿ self-report tool). Data (demographic, socioeconomic, and reported adherence) were collected in individual interviews with child-caregiver pairs. Additional adherence monitoring methods used for both groups included the Morisky-8-Item Medication Adherence Scale (MMAS-8) and a facility based pill count. FGDs were held with groups of caregivers and groups of children â‰¥13 years of age to understand reasons for non-adherence as well as issues around reporting non-adherence. Superiority testing was conducted by comparing adherent proportions and their confidence intervals (95% CI). Further concurrent validity test was done using the Mann-Whitney U test to evaluate the relationship between the new tool and the MMAS-8 scores. Agreement between the child and caregiver reports of adherence was used as a test of reliability of the new tool using the kappa statistic. Socio-demographic, clinical and care-related factors associated with adherence were identified using reported adherence in both child and caregiver groups in a logistic regression model. Two pill count methods were assessed for feasibility using the proportions of children with complete data for calculating adherence levels, and their CI and a comparison of the two methods, a routinely-used method and one that incorporated the reported residual quantity (RRQ) of medication at last refill. Results : Analysis included 245 child-caregiver pairs, 123 in the experimental group and 122 in the control group. The median age for children was 9 years. In the experimental group, adherence by caregiver and child reports ranged from 94.3% - 98.4% and 78.4% - 96.1%, and those in the control group ranged from 89.2% - 97.5% and 71.2% - 98.1%, respectively. There was no significant difference between adherence levels in the two groups. Adherence levels measured by both the experimental and control tools were found to be associated with MMAS-8 adherence levels (p <0.05). Agreement between child- and caregiver-reported adherence was moderate though significant (kappa; 0.407, p <0.05). Only about half of the children had adequate data to compute pill counts. Proportions adherent at 95% cut-off were 39% by the routine pill count"Ÿ and 58% by the Pill count RRQ"Ÿ. Being an orphan was associated with child reported-adherence whereas use of non-human reminders, having a maternal relative as a primary caregiver and knowledge of dose frequency, were all associated with caregiver-reported adherence. Major causes of non-adherence mentioned during the FGDs included interference of medication administration times with scheduling of routine socio-economic activities and lack of support from some non-biological caregivers. Reporting of non-adherence appeared to be hampered by perceptions of negative reactions by healthcare workers to these reports and by caregivers being unaware that the child missed some doses. Conclusions: The new 10-day tool"Ÿ was not shown to be superior to the PACTG-style tool"Ÿ in detecting non-adherence, however this new tool was found to be a valid and reliable adherence monitoring tool that included a moderately long recall period of 10 days, can be applied without the need for the respondent to remember names of individual medicines in the
Keywords: Uncatalogued